Navigating future disruptions: the impact of COVID-19 on accounting education in private universities in Nigeria - Asaleye, Abiola John; Inegbedion , Henry; Garidzirai , Rufaro (Society Register, 2024)
(Purpose) The COVID-19 pandemic caused unprecedented disruptions to global education, challenging teaching, research, and community engagement. This study examines these impacts on accounting education in private universities in Nigeria, focusing on preparedness for future crises. (Design/Methodology) A cross-sectional survey of 209 accounting professionals from Nigerian private universities explored disruptions in teaching, research, and community development. Descriptive and inferential statistics were used to evaluate their direct and indirect effects on performance indicators. (Findings) Community development showed the highest variability, while research exhibited the least. Teaching disruptions significantly increased ICT investment, demonstrating its role during the pandemic. However, no significant indirect pathways were found between ICT investment and disruptions in teaching or research, nor between ICT and performance indicators. (Originality/Value) This study uniquely investigates the dual impacts of pandemic-induced disruptions on accounting education in a developing economy on teaching, research, and community development. It shows the role of teaching in driving technological adaptation and provides critical insights into educational improvement in the future. (Conclusion) The COVID-19 pandemic influenced the tripartite missions of accounting education in Nigeria’s private universities, suggesting lessons for innovation and strategic preparedness against future disruptions; these findings contribute to global discussions on educational crisis management and resilience planning.